Hydroxyurea in the management of sickle cell disease: pharmacogenomics and enzymatic metabolism. Issue 6 (December 2018) - Yahouédéhou, Sètondji; Adorno, Elisângela; da Guarda, Caroline; Ndidi, Uche; Carvalho, Suellen; Santiago, Rayra; Aleluia, Milena; de Oliveira, Rodrigo; Gonçalves, Marilda
Abstract Hydroxyurea (HU) was approved to be used in the treatment of sickle cell disease (SCD) because of its anti-sickling potential. However, there is variability in HU response among SCD patients and this can be due to physiological, socioeconomic, environmental, metabolic and/or genetic factors. The present review focuses on the latter two. Three quantitative trait loci, HBG2, BCL11A andHMIP, have been suggested as important markers for HU response. Other genes (ASS1, KLF10, HAO2, MAP3K5, PDE7B, TOX, NOS1, NOS2A, FLT1, ARG1, ARG2, UGT1A1, OR51B5/6, SIN3A, SALL2, SAR1A, UTB, OCTN1, CYP2C9, AQP9, MPO, CYP2E1, andGSTT1 ) have also been considered. Studies implicate catalase, urease, horseradish peroxidase and enzymes of CYP450 family in HU metabolism. However, little is known about these enzymes. Therefore, further studies are needed to elucidate the metabolic pathway of HU, which will facilitate pharmacogenomic studies and help in identification of candidate genes for predicting HU response.